Effect of Biofertilizer on Productivity of Upland Rice (Oryza sativa L.) in Nagaland, India - Ovung, Zuchumi; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in the experimental research farm of School of Agricultural Sciences and Rural development (SASRD), Nagaland University during April to September 2011 to study the effect of different sources of organic nutrients on productivity of upland rice (Oryza sativa L.). The soil of the experimental field was sandy loam in texture, acidic in nature (4.6 pH) with high organic carbon (1.31%), low available N (153.87 kg ha-1), low available P (11.87 kg ha-1) and medium available K (236.12 kg ha-1). The treatments namely Sesbania aculeata @ 6.25 t ha-1, Green leaf manure @ 10 t ha-1, Paddy straw @ 10 t ha-1, Sesbania aculeata @ 6.25 t ha-1+Azotobacter@ 20 g kg-1 seed, Green leaf manure @ 10 t ha-1+Azotobacter@ 20 g kg-1 seed, Paddy straw @ 10 t ha-1+Azotobacter @ 20 g kg-1 seed and control were used in Randomised Block Design with 3 replication. The result of the experiment revealed that Sesbania aculeata @ 6.25 t ha-1+Azotobacter@ 20 g kg-1 seed significantly recorded maximum no of grains panicle-1 (173.14), no of panicles m-2 (163.43) and grain yield (30.88 q ha-1), giving highest gross return (rs. 33116.8) and net return (Rs.20366.8).